Unmasking misconceptions: an integrated framework of Socratic questioning and alternative assessment in chemistry education - Abdullah, Nabilah; Amdan, Arief Iskandar (Penerbit UiTM (UiTM Press), 2026)
Conventional chemistry assessments often emphasise factual recall over conceptual understanding, allowing misconceptions to persist undiagnosed and unaddressed. This study investigated the effectiveness of an integrated approach combining Socratic questioning with alternative assessments to reveal and address student misconceptions in chemistry. A single-group quasi-experimental design was implemented with 43 Malaysian Form Four students on the topics of acids, bases, and salts. The approach included a two-tiered multiple-choice diagnostic test, concept mapping, and semi-structured interviews with the participants. The results revealed that while post-test scores showed improvement, alternative assessments provided a more comprehensive picture of student understanding. Two-tiered items distinguished between valid reasoning and correct answers based on flawed logic. Concept maps exposed persistent, flawed knowledge structures, such as linking ‘salt’ directly to ‘neutral.’ The interviews revealed the origins of these misconceptions, including the tendency to conflate ‘strong’ with ‘concentrated’ based on everyday experiences. The study demonstrates that these alternative assessment tools complement each other in providing a holistic diagnosis of students ’understanding, revealing specific misconceptions that remain hidden in conventional scoring. The combined tools offer a complex view of student cognition that is unattainable through standard testing. A practical conceptual framework is proposed to help educators integrate Socratic dialogue with diagnostic assessment, shifting from assessment of learning to assessment for learning.